Drug release from thin films encapsulated by a temperature-responsive hydrogel. Issue 8 (30th January 2019) - Werzer, Oliver; Tumphart, Stephan; Keimel, Roman; Christian, Paul; Coclite, Anna Maria
Abstract : Temperature-controlled release and study on the effects of the drug–polymer interaction and pH. Abstract : Control over drug delivery may be interestingly achieved by using temperature responsive encapsulants, which change their thickness and mesh size with temperature. The prototype N -isopropylacrylamide hydrogel cross-linked with di(ethylene glycol) divinyl ether p(NIPAAm- co -DEGDVE) swells at low temperature and collapses above the lower critical solution temperature (LCST), ∼29 °C in a buffer. It might be expected that drug release from such encapsulation is always favored below the LCST, due to the larger free volume present in the swollen polymer film. Recent results show contradicting behavior where some cases behave as expected and others release much less when the polymer layer is swollen. In this study, layers of the drugs phenytoin, clotrimazole and indomethacin were drop cast on glass and p(NIPAAM- co -DEGDVE) layers were then synthesized directly on top of these drug layers via initiated chemical vapor deposition (iCVD), a solvent-free and gentle polymerization technique. Dissolution experiments were then performed, in which the drug release through the hindrance of the hydrogel was measured at different pH values. The results show that not only the swelling but also the permeate (drug in this case)–polymer interaction plays an important role in the release.